2021
DOI: 10.1111/lasr.12574
|View full text |Cite
|
Sign up to set email alerts
|

Represented but unequal: The contingent effect of legal representation in removal proceedings

Abstract: Substantial research and policymaking have focused on the importance of lawyers in ensuring access to civil justice. But do lawyers matter more in cases decided by certain types of judges than others? Do lawyers matter more in certain political, legal, and organizational contexts than others? We explore these questions by investigating removal proceedings in the United States—a court process in which immigration judges decide whether to admit noncitizens into the United States or deport them. Drawing on over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Applying the crisis-jurisprudence framework to immigration adjudication promises to yield important new insights. Consistent with findings from the broader research on judicial decision-making (Epstein et al, 2013;Harris & Sen, 2019;Rachlinski & Wistrich, 2017), research on IJs has found that extralegal factors may also play an important role in immigration case outcomes (Chand et al, 2017;Kim & Semet, 2020;Rottman et al, 2009;Ryo & Peacock, 2021). More nascent is research on immigration adjudication and bias.…”
Section: Crisis Jurisprudence Immigration Courts and Biasmentioning
confidence: 74%
See 2 more Smart Citations
“…Applying the crisis-jurisprudence framework to immigration adjudication promises to yield important new insights. Consistent with findings from the broader research on judicial decision-making (Epstein et al, 2013;Harris & Sen, 2019;Rachlinski & Wistrich, 2017), research on IJs has found that extralegal factors may also play an important role in immigration case outcomes (Chand et al, 2017;Kim & Semet, 2020;Rottman et al, 2009;Ryo & Peacock, 2021). More nascent is research on immigration adjudication and bias.…”
Section: Crisis Jurisprudence Immigration Courts and Biasmentioning
confidence: 74%
“…The current study also contributes to research on judicial decision-making and bias (Chand et al, 2017;Epstein et al, 2013;Harris & Sen, 2019;Ryo & Peacock, 2021). In particular, we develop a new understanding of "crisis jurisprudence" (Light et al, 2019) by advancing a new perspective on judicial bias that integrates insights from the study of stigma and stigmatization.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Research on the role of legal representation for noncitizens' outcomes in immigration legal system proceedings has found a similar relationship: having an attorney is correlated with more favorable legal outcomes in deportation proceedings in U.S. immigration courts, also known as the “representation effect” (Ryo & Peacock, 2021). Past studies using both observational and quasi‐experimental analytic approaches have found that having an attorney increases immigrants' chances of receiving bond from detention (Ryo, 2016, 2018), defensive asylum claims in immigration court (Keith et al, 2013; Schoenholtz et al, 2007), affirmative asylum claims (Schoenholtz et al, 2014), and relief from removal (Eagly & Shafer, 2015).…”
Section: Literature Reviewmentioning
confidence: 95%
“…For undocumented or liminally documented immigrants in the U.S. seeking long‐term, stable legal status or fighting against their removal in immigration court, having access to an attorney can increase their chances of winning their claims. Several quantitative studies have empirically confirmed this “representation effect” (Chand et al, 2021; Eagly & Shafer, 2015; Miller et al, 2015; Ryo, 2016, 2018; Ryo & Peacock, 2019) or “the increased probability of a favorable outcome associated with legal representation” (Ryo & Peacock, 2021, p. 634). At the same time, however, scholars acknowledge that we do not fully understand the causal mechanisms underlying this relationship, or the degree to which lawyers' case selection accounts for case outcomes.…”
Section: Introductionmentioning
confidence: 97%